Գորգը Հայ Առաքելական Եկեղեցու արարողակարգերում - Պօղոսեան, Աշխունջ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
У армян ритуальные особенности ковра выражаются в традиционном гостеприимстве, в свадебных и похоронных обрядах, в процессе изготовления ковра и так далее. На самом деле ковер изначально воспринимался как некий мифический предмет, безопасное и освященное пространство на котором может сидеть или стоять главный жрец, а позже и вождь племени. Ковру приписывались определенные ритуально-магические особенности, благодаря которым освященный ковер воспринимался как один из символов культа плодородия и возрождения природы и в этом аспекте считался одним из атрибутов богини Анаит. После принятия в Армении христианства в качестве государственной религии, наряду с другими дохристианскими обычаями и обрядами, в виде пережиток, продолжали существовать ритуально-магические особенности ковра. В этом смысле особенно примечательно изображение Богородицы на центральной тимпане монастыря Нораванк. Там над троном расстелен ковер, на котором восседает Богородица. Особое ритуальное значение придавалось ковру в процессе изготовления мира. Сведения из письменных и изобразительных источников, полевые этнографические материалы дают нам возможность выявить пережиточные проявления ритуально-магических особенностей, приписываемых ковру в дохристианских верованиях, в обрядах Армянской Апостольской Церкви. Думается, что одним из пережитков некогда существовавшего представления о священном пространстве ковра является то, что традиционно, каждому из духовных классов Армянской Апостольской Церкви в соответствии с их статусом был выделен особый ковер. Известны также католиковские ковры, украшенные изображениями орлов, которые, повидимому, представляют раннехристианские традиции. В целом, можно предположить, что во всех случаях они должны были характеризоваться подходящими деталями декора, красками и смысловым содержанием, что присуще данному классу. Among the Armenians, the ritualistic features of carpets are expressed in traditional hospitality, weddings and funerals, in the rituals performed during carpet making, and in other ceremonies. In fact, the carpet was originally perceived as a certain mythical object, a safe and sanctified area, on which the chief priest and later the chief of the tribe could sit or stand. The carpet was attributed certain ritualistic properties, due to which the sacred carpet was perceived as one of the symbols of fruitfulness and fertility and as such had a special significance in the rituals and ceremonies related to the worship of the mother deities, particularly the goddess Anahit. Even after the adoption of Christianity as the state religion in Armenia, their remnants continued to exist in a modified form, along with other pre-Christian customs and rituals. The information collected by us from written and pictorial sources, and ethnographic field materials have made it possible to discover the expressions of ritual features attributed to the carpet in the pre-Christian beliefs, in the rites of the Armenian Apostolic Church. The image of the Virgin Mary on the central tympanum of the Church of Noravank is particularly noteworthy in this sense. There is a carpet over the throne, on which Our Lady is seated. A special ritual significance was attached to the carpet in the process of making the Holy Myron. In those episodes, the immaculate and safe perception of the sacred area of the carpet is the most symbolic. We think that one of the responses to the once rooted notions about the sacred area of the carpet is that traditionally, each of the spiritual classes of the Armenian Apostolic Church was allocated a special carpet according to their status. In this regard, the carpet made in 1731 by the order of Catholicos Nerses III, Head of the Armenian Church of Aghvank is famous. Catholicossal carpets decorated with images of eagles are also known, which apparently represent early Christian traditions. In general, it can be assumed that in all cases carpets should have been characterized by suitable decoration details, colors and semantic content, which is inherent in the given class. Prayer rugs also existed.
Keywords: Կրօնագիտութիւն